2020
DOI: 10.1016/j.asr.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a long-duration AR throughout five solar rotations: Magnetic properties and ejective events

Abstract: Coronal mass ejections (CMEs), which are among the most magnificent solar eruptions, are a major driver of space weather and can thus affect diverse human technologies. Different processes have been proposed to explain the initiation and release of CMEs from solar active regions (ARs), without reaching consensus on which is the predominant scenario, and thus rendering impossible to accurately predict when a CME is going to erupt from a given AR. To investigate AR magnetic properties that favor CMEs production,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(121 reference statements)
1
1
0
Order By: Relevance
“…Therefore, we found that EUV intensity evolution of the AR could be a proxy for the total magnetic flux evolution. This is in agreement with other results that studied the long-term evolution of EUV intensities of several ARs in solar cycle 24 (Ugarte- Urra et al 2015;Iglesias et al 2020). However, we could not find any clear signature of a flare precursor in the EUV intensity evolution of the flaring ARs prior to the flares.…”
Section: Euv Intensity Evolutionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, we found that EUV intensity evolution of the AR could be a proxy for the total magnetic flux evolution. This is in agreement with other results that studied the long-term evolution of EUV intensities of several ARs in solar cycle 24 (Ugarte- Urra et al 2015;Iglesias et al 2020). However, we could not find any clear signature of a flare precursor in the EUV intensity evolution of the flaring ARs prior to the flares.…”
Section: Euv Intensity Evolutionsupporting
confidence: 93%
“…Ugarte-Urra et al (2015) found the lifetimes of several ARs to be continuously proportional to the maximum 304 Å intensity. Recently, Iglesias et al (2020) studied longterm evolution of a long-duration AR in the early phase of solar cycle 24 and found that its characteristics varied significantly during five solar rotations.…”
Section: Introductionmentioning
confidence: 99%
“…The present results show that its validity can not be simply extended to recurrent active regions because in the domains of very long lifetimes and very large areas the relationship is more complex as is illustrated by Figure 4. Iglesias et al [13] followed a recurrent sunspot group in 1990. In my data its maximum umbral area was 78, it is a relatively small group.…”
Section: Discussionmentioning
confidence: 99%
“…The proxy is given by an empirical power-law relationship between the total photon flux in 304 Å and the total unsigned magnetic flux. This method was shown to be sufficient to obtain accurate information about active regions emerging on the far side of the Sun, and was employed to study the continuous long-term evolution of active region magnetic flux (Ugarte- Urra et al 2015Urra et al , 2017Iglesias et al 2019).…”
Section: Revised Flux-luminosity Relationshipmentioning
confidence: 99%